2021
DOI: 10.1186/s43014-021-00079-5
|View full text |Cite
|
Sign up to set email alerts
|

High-yield production of secoisolariciresinol diglucoside from flaxseed hull by extraction with alcoholic ammonium hydroxide and chromatography on microporous resin

Abstract: This study used alcoholic ammonium hydroxide to directly hydrolyze and extract secoisolariciresinol diglucoside (SDG) from flaxseed hull in a one pot reaction. The optimal extraction conditions, including the concentration of ammonium hydroxide, extraction time, and temperature, were examined in single factor experiments, followed by response surface methodology (RSM) with 3-level, 3-factor Box-Behnken experiments. As a result, the optimal extraction conditions were determined as follows: material-liquid ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The phytoestrogens (flax seed lignans and soy isoflavones) are often found in the human diet. A number of studies employing dietary flaxseeds have been carried out to date, and the results showed that SDG lignan may reduce plasma cholesterol concentrations (Noreen, Rehman, et al, 2023; Nwozo et al, 2023; Zhuang et al, 2021). The purpose of this study was to evaluate the effectiveness of SDG + anethole‐enriched cookies for hyperlipidemic patients having high range of total cholesterol (>220 mg/dL), total triglyceride (>150 mg/dL), and low‐density lipoprotein (>130 mg/dL).…”
Section: Introductionmentioning
confidence: 99%
“…The phytoestrogens (flax seed lignans and soy isoflavones) are often found in the human diet. A number of studies employing dietary flaxseeds have been carried out to date, and the results showed that SDG lignan may reduce plasma cholesterol concentrations (Noreen, Rehman, et al, 2023; Nwozo et al, 2023; Zhuang et al, 2021). The purpose of this study was to evaluate the effectiveness of SDG + anethole‐enriched cookies for hyperlipidemic patients having high range of total cholesterol (>220 mg/dL), total triglyceride (>150 mg/dL), and low‐density lipoprotein (>130 mg/dL).…”
Section: Introductionmentioning
confidence: 99%